The characteristic expression of circulating MicroRNAs in osteoporosis: a systematic review and meta-analysis - Gao, Jie; Zhang, Xiuzhen; Ding, Jing; Zhang, Houli; Zhang, Xu; Jiang, Juan; Chen, Wenwen (Frontiers in Endocrinology, 2024)
Objective: To evaluate the characteristics of the circulating microRNAs expression profile in patients with osteoporosis. Methods: A systematic literature search was performed using the databases of Web of science, PubMed, Embase, Cochrane library, CNKI, VIP and WANFANG from inception until March 1, 2024. The search strategy employed keywords encompassed "osteoporosis or bone loss or osteopenia" and "miRNA or microRNA". The NOS quality assessment scale was used to evaluate methodological quality. Heterogeneity tests and statistical analyses of all data were performed by Stata 16.0. The differences in microRNA levels between groups were illustrated by the weighted mean difference (WMD) and 95% confidence interval (95% CI). Results: Total of 27 studies were included and analyzed in the meta-analysis, with 2263 participants. The results showed that miR-21-5p (WMD 0.88, 95% CI: 0.22 to 1.55), miR-125b-5p (WMD 6.63, 95% CI: 0.19 to 13.08), miR-483-5p(WMD 6.43, 95% CI: 3.26 to 9.61), miR-133a (WMD 1.43, 95% CI: 1.39 to 1.47), miR-422a (WMD 1, 95% CI: 0.28 to 1.72) and miR-214-3p (WMD 2.03, 95% CI: 0.14 to 3.92) were up-regulated significantly, and miR-497-5p (WMD -0.57, 95% CI: -0.98 to -0.17) was down-regulated significantly. Conclusion: MiR-21-5p, miR-125b-5p, miR-483-5p, miR-133a, miR-497-5p, miR-422a, and miR-214-3p might serve as potential diagnostic biomarkers of osteoporosis. In the further, integrating these miRNAs to build diagnostic model might be promising diagnosis strategy for osteoporosis.